Molecular Docking Studies of Schiff Bases with Azetidinone Against Dihydrofolate Reductase Enzyme as Potential Anti-cancer Agents (Asian Journal of Pharmaceutics (AJP), 2024)
Background: In recent times, cancer has emerged as a major health concern. It was established that everyantagonist of the dihydrofolate reductase exhibits anti-cancer activity. For anti-cancer action, several Schiff-basedderivatives with azetidinone rings were designed and docked against the dihydrofolate reductase protein (PDBid:6CXK) in the current work. The ligands were compared to those of standard antagonists of dihydrofolatereductase, that is, trimethoprim and pyrimethamine. Materials and Methods: The ligands were drawn in.molformat using ChemSketch software and converted to.pdb format using Avogadro software. The iGEMDOCKsoftware was utilized to conduct molecular docking investigations, and Discovery Studio Visualizer was ultimatelyused to visualize the results. Results and Discussion: Most compounds have demonstrated a better affinity forbinding to the dihydrofolate reductase. Most of the ligands have demonstrated nearly the same binding affinitiesas that of the standard dihydrofolate reductase, such as trimethoprim (−102.1 kcal/mol) and pyrimethamine(−91.8 kcal/mol). The top 2 compounds 3A8B (−100.6 kcal/mol) and 3A9B (−94.6 kcal/mol) were chosen forvisualization. Conclusion: Schiff base derivatives with azetidinone ring have the potential to be a promisingclass of drugs for the treatment of anti-cancer action since they have a higher binding affinity to the dihydrofolatereductase than standard antagonists.